PENGARUH KEPEMIMPINAN MANAJEMEN SEKOLAH DAN PROFESIONALISME GURU TERHADAP KINERJA GURU SMK WACHID HASYIM 2 SURABAYA - Andini Zahra Adystia; Nugroho Mardi Wibowo (Jurnal Manajerial Bisnis, 2023)
This study aims to determine and analyze the influence of school management leadership and teacher professionalism on teacher performance at SMK Wachid Hasyim 2 Surabaya. A quantitative approach was used in this study with a population of 34 people and using a saturated sample so that the entire population became research respondents. The results of the study show that simultaneously, school management leadership and teacher professionalism have a significant influence on teacher performance. Partially, school management leadership and teacher professionalism have a significant influence on teacher performance, and teacher professionalism has a dominant influence on teacher performance.